Are visual PINs the next step in authentication?. (February 2020) - Anderson, Geoff
Abstract : Identity has always been a crucial component in how we interact with the world. How we prove our identity is even more important. Whether it is getting permission to take money out from your bank, gaining access to your Netflix account to watch the latest Black Mirror series, or just being able to log on to Twitter to add a comment – these all require proof that we are who we say we are.